PERBEDAAN HASIL BELAJAR KIMIA SISWA MENGGUNAKAN MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) DENGAN MEDIA MIND MAPPING DAN MOLYMOOD PADA POKOK BAHASAN HIDROKARBON - Ratna Sari Dewi (Pascasarjana Universitas Negeri Medan, 2015)
Abstract This research was purpose to know the effect of TGT (Team Games Tournament) learning model with Molymood to student chemistry learning outcomes on teaching Hydrocarbon. The type of this research is quasy-experiment using random group pretest-posttest design. The 2 class of X students of some SMA Negeri in Medan used as a sample, a class was teach by TGT model using mind mapping media and another with molymood media. The research data analysed using two side T-test. The research result show that there is a differences of student learning outcomes between student teach using TGT model with mind mapping media accompanying molymood media. It shows that the student teaching by TGT model using molymood give increasing learning output approx 70.9%, while TGT model with mind mapping media 54.2% Keyword: Teams Games Tournaments (TGT), Mind Mapping, Molymood, Hydrocarbon